2012
DOI: 10.22342/jims.15.2.50.105-111
|View full text |Cite
|
Sign up to set email alerts
|

Robust Decline Curve Analysis

Abstract: Abstract. Empirical decline curve analysis of oil production data gives reasonable answer in hyperbolic type curves situations; however the methodology has limitations in fitting real historical production data in present of unusual observations due to the effect of the treatment to the well in order to increase production capacity. The development of robust least squares offers new possibilities in better fitting production data using decline curve analysis by down weighting the unusual observations. This pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…They presented a more accurate approach by combining exponential and hyperbolic declines into one new model. Darwis et al (2009) used DCA to develop three models by using historical data and least squares techniques. Peak oil models forecast is another way of predicting future oil production and oil reserves, several models are available that uses this approach (Lianyoung et al (2008); Wang et al (2011)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…They presented a more accurate approach by combining exponential and hyperbolic declines into one new model. Darwis et al (2009) used DCA to develop three models by using historical data and least squares techniques. Peak oil models forecast is another way of predicting future oil production and oil reserves, several models are available that uses this approach (Lianyoung et al (2008); Wang et al (2011)).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of a Duong power law model and the Valko stretched-exponentdecline model (SEDM) were compared with a conclusion that a systematic comparison of results from multiple models would be beneficial to assess uncertainty in the estimate of reserves(Denney, 2012). The addition of a regression analysis technique to the standard method of least squares fit for the exponential decline curve can provide a better fit and representation of historical production(Darwis et al, 2009). Finally, it has been found that the application of a logistic growth model, originally designed to project population growth, produces realisticDownloaded by [Umeå University Library] at 18:25 18 November 2014…”
mentioning
confidence: 99%